Ending hunger in Africa: prospects for the small farmer - Runge, C. Ford; Senauer, Benjamin; Pardey, Philip G.; Rosegrant, Mark W. (International Food Policy Research Institute, 2004)
In contrast to widely held uncertainties about Sub-Saharan Africa's ability to meet the Millennium Development Goals (MDGs), recent successes in African smallholder farming show that agriculture could play a key role in helping the region reach those goals. African governments and the donor community have recognized this potential and have pledged to help generate agricultural progress. This policy brief considers recent trends in poverty, malnutrition, and growth; outlines some of the challenges to boosting agricultural growth; and highlights cases of agricultural success in specific countries. By learning from case studies of smallholder success and building on the new enthusiasm of African governments, donors and their African partners can ensure that agriculture's role in meeting the MDGs is fully realized." -- from Text